Optimizing Public Administration Strategies for Enhancing Access, Quality, and Equity in Education Systems - Dermawan, Wawan; Arkam, Muh.; Suparadi, Suparadi (Journal Social Civilecial, 2023)
This study examines the role of public administration in improving access, quality, and equity in education systems. Education is a fundamental tool for socio-economic development, yet disparities persist globally, particularly among marginalized groups. The research focuses on the effectiveness of public policies and administrative strategies in addressing these challenges. Through a mixed-methods approach, the study analyzed data collected via a structured questionnaire, assessing the impact of policy decentralization, performance-based funding, and inclusive educational initiatives on educational outcomes. The findings reveal that decentralizing educational governance and promoting community involvement significantly improve access and quality, while performance-based funding enhances accountability and efficiency in educational institutions. Additionally, targeted interventions for marginalized groups, such as gender-sensitive policies and support for children with disabilities, contribute to greater equity. The results highlight that public administration is essential in shaping education systems that are responsive to the needs of diverse learners. This research fills a gap in the literature by offering a comparative analysis of effective public administration practices in education, particularly in developing countries. The study provides actionable recommendations for policymakers and educators to strengthen education systems through strategic governance.